Influence of bentonite fining on protein composition in wine. (January 2017) - Jaeckels, Nadine; Tenzer, Stefan; Meier, Miriam; Will, Frank; Dietrich, Helmut; Decker, Heinz; Fronk, Petra
Abstract: Bentonite is the only fining agent which can stabilize wine and prevent protein haze formation after bottling. Currently many approaches are used to find an alternative because of bentonite's negative influence on color and aroma compounds. Nevertheless, the interaction of bentonite with wine proteins is not fully understood. Therefore, we analyzed the influence of a NaCa-combined bentonite on the protein content and composition of different wines showing a partial selectivity on protein adsorption. For example, glycosylated proteins were not removed by bentonite in notable amounts. Performing mass spectrometry we were able to demonstrate that 96% of class IV chitinase was adsorbed by bentonite, whereas varying adsorption behavior was observed for different thaumatin-like protein isoforms ranging from no removal to 98% of reduction. These differences may be explained by considering hydrophobicity surface of the proteins. Here, some differences are detected which might be an explanation for the better or worse adsorption. Our results demonstrate the importance to consider the isoforms of the potential haze-related proteins. Only the understanding of the interaction conditions of the wine component and their behavior with fining agents might result in the development of new strategies preventing protein haze formation. Highlights: Adsorption behavior of bentonite varies for different TLP isoforms. Bentonite has good adsorption properties concerning haze-related chitinase. Surface properties of proteins influence adsorption behavior.